The efficacy of chlorhexidine gel in the prevention of alveolar osteitis after mandibular third molar extraction: a systematic review and meta-analysis - Amare Teshome (BMC, 2017)
Abstract Background Alveolar osteitis is a very painful and distressing condition for a patient who has recently undergone a tooth extraction and has led dental professionals to search for preventive measures. The aim of this meta-analysis to determine the effect of chlorhexidine (CHX) gel on the incidence of alveolar osteitis after mandibular third molar extraction. Methods Studies were searched for on electronic search engines using Medline (PubMed), Cochrane central, Scopus and advanced Google Scholar from May 2015 to December 2015. Randomized controlled trial studies with a history of mandibular third molar extraction, along with the administration of topical chlorhexidine gel were included. The risk of bias of the selected articles was assessed using the Cochrane risk of bias assessment tool. RevMan 5.3 Software was used to analyze the pooled effect. I2 was calculated to determine heterogeneity and a funnel plot was used to check the risk of bias. Subgroup analysis was also done based on the presence of confounding factors (smoking, oral contraceptive etc.) and on split mouth design. Results Out of 52 articles, ten met the inclusion criteria. 862 participants were involved in the selected studies with a mean age range from 24.15 ± 5.02 to 36.65 ± 11. The overall RR was 0.43 (95% CI: 0.32, 0.58, p < 0.00001). Three studies used a split-mouth design to check the effect of chlorhexidine gel in the prevention of alveolar osteitis incidence. There was a pooled effect of 0.29 (95% CI: 0.16, 0.50) for the intervention group in the split mouth design studies. A stratified analysis was done to check the effect of CHX gel in patients with confounding factors and a significant reduction of AO incidence was found; 0.60 (95% CI: 0.41, 0.87; p = 0.05) in the intervention. There was no reported adverse reaction. The heterogeneity (I2) was 40%. The funnel plot showed that there was no significant publication bias. Conclusion This meta-analysis suggests that CHX gel is superior to a placebo in reducing the incidence of alveolar osteitis after mandibular third molar extraction.